Changes in certain blood constituents in cases of canine venereal granuloma - Singh, Umesh; Singh, L N (The Indian Journal of Animal Sciences, 2012)
Change in Â biochemical profile of blood in cases of canine vencreal granuloma were studied using 13 venerealgranuloma cases and 8 normal bitches. Total serum protein concentration did not differ significantly from normalapparently healthy aninmals but the albium levels decreased and globulin levels increased significantly resulting insignilicantly low A/G ratio in tumor bearing animals. Total sialic acid, lipid associated sialic acid, bound sialic acid, freesialic acid, calcium and protein bound hexose in blood serum of the affected animals were found to increase significantly.While blood glucose concentration was significantly low. The levels of albumin, A/G and total sialic acid in serumcould he used as convenient markers for prognosis of such diseased cases.